EFEKTIVITAS ASISTENSI MENGAJAR DALAM MENIGKATKAN KUALITAS DALAM PEMBELAJARAN DI SDN 1 AIKMEL UTARA 2024 - Rizaldo, Enki; Mirwan Apriandi, Muhammad; Suriani, Lilik; Anggraini, Sapma Dewi; Apriantari, Baiq Risa; Astuti, Maeli (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
Teaching assistance is a strategic program to increase the effectiveness of the learning process through mentoring in the classroom. This study aims to analyze the role of teaching assistants, their impact on student learning, and the challenges faced in the implementation of the program at SDN 1 Aikmel Utara. The research uses a qualitative descriptive method with a case study approach, involving teachers, teaching assistants, and students as the main informants. Data collection techniques include direct observation, semi-structured interviews, and document analysis. The results show that teaching assistants play a significant role in supporting classroom management, guiding students who need additional help, and creating an interactive learning atmosphere